2020
DOI: 10.1371/journal.pone.0231009
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the mitochondrial CO1 gene in native and invasive populations of Harmonia axyridis Pall. comparative analysis

Abstract: Our study is focused on original and publicly accessible data on the intraspecific variability of the barcoding DNA fragment in ladybirds Harmonia axyridis Pall analysis. The complete dataset consists of 39 haplotypes, 16 of which we identified for the first time. The intra-population and geographical variability of the barcoding fragment was studied for seven populations of the western and eastern groups of the native range and in six invasive populations, in which 25 of the 39 haplotypes are found. Populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…For example, within the species D. adelpha and D. limitata, haplotypes were separated by 53 and 28 SNVs, respectively (Figure 2). The publicly available CO1 sequences for D. biannularis, D. balteata, D. speciosa, and D. tibialis were, by contrast, similar to what is generally observed for intraspecific variability in beetles and other insects (49,63), although increased sampling is needed to more fully describe the nucleotide variability in these Diabrotica lineages. Given the discrepancies observed between taxonomic designation and CO1 haplotypes, both here and in other phylogenetic appraisals of Diabrotica and allied species (22), a concerted effort should be made to better understand how the sorting and evolution of mitochondrial and other genetic and genomic data corresponds to morphological, behavioral, and adaptive divergence.…”
Section: Discussionsupporting
confidence: 57%
“…For example, within the species D. adelpha and D. limitata, haplotypes were separated by 53 and 28 SNVs, respectively (Figure 2). The publicly available CO1 sequences for D. biannularis, D. balteata, D. speciosa, and D. tibialis were, by contrast, similar to what is generally observed for intraspecific variability in beetles and other insects (49,63), although increased sampling is needed to more fully describe the nucleotide variability in these Diabrotica lineages. Given the discrepancies observed between taxonomic designation and CO1 haplotypes, both here and in other phylogenetic appraisals of Diabrotica and allied species (22), a concerted effort should be made to better understand how the sorting and evolution of mitochondrial and other genetic and genomic data corresponds to morphological, behavioral, and adaptive divergence.…”
Section: Discussionsupporting
confidence: 57%
“…Haplotype diversity estimated from single DNA locus (mitochondrial DNA) reveals a reduced number of haplotypes among invasive populations as compared to the native ones (Blekhman et al, 2020) confirming their most likely same NAM origin (Blekhman et al, 2020;Lombaert et al, 2010). Diversity estimates from multilocus microsatellites support the role of introduction modalities with lower allelic richness in single introductions from NAM (SAM and SAF) and higher expected heterozygosity in EU than in both parents (BIO and NAM) .…”
Section: Demo-genetic Dynamics Of the Introductionmentioning
confidence: 78%
“…Figures adapted from cited literature. References [1] Lombaert et al (2010); [2] Blekhman et al (2020); [3] Lombaert, Guillemaud, et al (2014)); [4] Facon, Hufbauer, et al (2011)); [5] Facon, Crespin, et al (2011)); [6] Turgeon et al (2011); [7] Tayeh et al (2013); [8] Laugier, (2013).…”
Section: The Impact Of Introduction Modalitiesmentioning
confidence: 99%
“…Analysis of mitochondrial CO1 of H . axyridis showed significant differences between the eastern and western populations in the native Russian range, suggesting that all populations in the invaded North American and European regions originated from populations from eastern Asia ( Blekhman et al 2020 ). Examination of single-copy nuclear genes of H. axyridis populations across mainland China and North America, South America, and Europe indicated that the genetic diversity in China was higher than that in North America and Europe, but lower than that in South America ( Li 2020 ).…”
Section: Comparative Studies To Quantify Differences In Native and Nomentioning
confidence: 99%